Effect of specimen geometry in tensile split Hopkinson pressure bar test - Huang, Mengping. (2009)
There are three types of Split Hopkinson Pressure Bar (SHPB) apparatus available in the strength of materials laboratory of Nanyang Technological University (NTU). They are used to obtain the torsion, compression and tension mechanical properties of various of materials under high strain rate. The tensile SHPB is used to measure the dynamic stress and strain response at high strain rate from 102 to 104 S-1 under tension. Its theory is based on the propagation of longitudinal stress waves along the elastic bars. Strain gauges are mounted on the input and output bars, raw data is obtained through oscilloscope transfer the voltage signal readings from strain gauges to obtain the raw data. After data acquisition, stress-strain, strain rate-time and strain-time curves are obtained for comparison with existing literature reviews. The main objectives of the project is to design the fixture to install the photo diode and use it to measure the speed of striker bar, alignment of SHPB by performing empty runs, calibration of SHPB using standard specimen Al6061-T6 at varying the insertion distance at 100, 300, 500 and 700mm and investigate result whether comparable with literature review. The project will also look into effects on the mechanical properties of the material Al6061-T6 with varying the geometry (Diameter) under high strain rate and also varying the insertion distance of the striker bar which giving varying impact velocities. Finally, recommendations will be proposed to improve the quality of the experimental results.